The Utilization of System Dynamics for House Pricing Analysis in Malaysia - Hashim, Zakiah; Sapiri, Hasimah; Misiran, Masnita; Abdul Halim, Tisya Farida (ExcelingTech Publishers, London, UK, 2018)
An increasing demand for residential housing has been a debate globally due to rapid economic development, particularly in Malaysia. The housing price appreciation showed steep increase both in urban and rural areas. Therefore, most of the people are afraid that they are unable to cope with such a high property prices. Even with the housing prices almost hitting the sky, yet the real factors as well as its causal effects are still open to question. Thus, this paper presents a system dynamics model of housing prices in Malaysia to identify the causality among related factors.The model expects the rising of population and strong growth in inflation in the long run that will affect housing prices significantly. As this dynamic model is expected to portray the main interacting variables, their causal effects can provide guideline for better intervention measures, in particular for the policy improvement in near future